Methotrexate use is safe in children with acute lymphoblastic leukemia - Utomo, Febriansyah Nur; Yulistiani, Yulistiani; Zairina, Nun; Permono, Bambang (Folia Medica Indonesiana, 2017)
Monitoring level of methotrexate is not only aimed at monitoring effectiveness, but also safety aspects of the administration of high-dose methotrexate because the use of high-dose methotrexate is one of the problems associated with toxicity in various organs. In the use of high-dose methotrexate, measurement of methotrexate is important to identify patients with a high risk of toxicity, particularly nephrotoxicity as well as for dosing guidelines for leucovorin therapy. The aim of this study was to analyze the safety of high-dose methotrexate on kidney function during chemotherapy consolidation phase in children with acute lymphoblastic leukemia. This was a longitudinal, observational prospective study conducted to determine the safety profile of high-dose methotrexate on kidney function during chemotherapy consolidation phase in children with acute lymphoblastic leukemia. Patients who met the inclusion criteria were given high-dose methotrexate according to the 2013 Indonesian ALL Chemotherapy Protocol. Measurement of methotrexate level and kidney function was done 3 times on each cycle of chemotherapy consolidation phase. Measurements were made on the 0, 24 and 48 hours after the first drop of high-dose methotrexate. This study had been reviewed by Ethics Committee of Dr. Soetomo Hospital Surabaya. There were 12 patients who met inclusion criteria and 6 patients among them had finished their chemotherapy consolidation phase completely. There was no significant change in kidney function after the administration of high-dose methotrexate compared to baseline (p>0.05) and there was no significant correlation between serum level of methotrexate versus creatinine clearance. In conclusion, methotrexate was safe to use in children with acute lymphoblastic leukemia.